2017
DOI: 10.1371/journal.pone.0185943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AAV-mediated knockdown of nNOS and GPx-1 gene expression in rat hippocampus after traumatic brain injury

Abstract: Virally mediated RNA interference (RNAi) to knock down injury-induced genes could improve functional outcome after traumatic brain injury (TBI); however, little is known about the consequences of gene knockdown on downstream cell signaling pathways and how RNAi influences neurodegeneration and behavior. Here, we assessed the effects of adeno-associated virus (AAV) siRNA vectors that target two genes with opposing roles in TBI pathogenesis: the allegedly detrimental neuronal nitric oxide synthase (nNOS) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Therefore, our results indicate that the positive modulation of Gpx1 expression would be a key component for the protection afforded by (PhSe) 2 in HT22 cells. It should be mentioned the importance of GPx activity, since its decrease promote susceptibility to oxidative stress by allowing the accumulation of harmful oxidants [58] , [59] , and because other selenoproteins cannot replace its function in protecting from generalized oxidative stress [5] . Gpx4 gene expression was not upregulated after (PhSe) 2 incubation and the results of decrease observed in the mtGpx4 expression would not represent a biological significance event according to functional thresholds used in quantitative PCR analyses [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results indicate that the positive modulation of Gpx1 expression would be a key component for the protection afforded by (PhSe) 2 in HT22 cells. It should be mentioned the importance of GPx activity, since its decrease promote susceptibility to oxidative stress by allowing the accumulation of harmful oxidants [58] , [59] , and because other selenoproteins cannot replace its function in protecting from generalized oxidative stress [5] . Gpx4 gene expression was not upregulated after (PhSe) 2 incubation and the results of decrease observed in the mtGpx4 expression would not represent a biological significance event according to functional thresholds used in quantitative PCR analyses [60] .…”
Section: Discussionmentioning
confidence: 99%
“…To test if CM could be neuroprotective in a rodent model of TBI, the number of dying/injured, Fluoro-Jade-positive neurons in the rat hippocampus was determined as previously described in Boone et al, [ 27 ]. Briefly, animals were survived for 24 hours, sacrificed and brains dissected out and frozen immediately on dry ice.…”
Section: Methodsmentioning
confidence: 99%
“…10ÎŒm coronal rat brain tissue sections were collected on Superfrost Plus slides, every 15 th section for 10 sections through the hippocampus. Sections were stained with 0.0001% FJC (a marker for neuronal injury) and neurons were counted in the CA1/2 & CA3 regions using stereological methods [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional testing was not performed in this experiment, but a similar study silencing IRF5 in macrophages in a mouse model of SCI found significant motor recovery as well as decreases in demyelination and inflammation (Li et al, 2016 ). Another experiment silencing nitric oxide synthase in a TBI model showed decreased neuronal degeneration in addition to improved working memory (Boone et al, 2017 ). As of now, most experiments using RNAi in TBI models focus on minimizing post-injury edema (Fukuda and Badaut, 2013 ; Xu et al, 2014 ; Guan et al, 2020 ).…”
Section: Translational Approaches In Animal Modelsmentioning
confidence: 99%